2015
DOI: 10.1073/pnas.1510045112
|View full text |Cite
|
Sign up to set email alerts
|

IL-7R signaling in regulatory T cells maintains peripheral and allograft tolerance in mice

Abstract: Foxp3 + CD4 + regulatory T cells (T reg ) have a crucial role in controlling CD4 + T-cell activation, proliferation, and effector function. However, the molecular mechanisms regulating T reg function remain poorly understood. Here we assessed the role of IL-7, a key cytokine regulating T-cell homeostasis, in suppressor capacity of T reg . Using a skin allograft model in which transplant acceptance is controlled by the number of transferred T reg , we find that T reg impair the proliferation of allogeneic CD4 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…They also confirm relevance in human melanoma patients, in terms of VEGF-C correlating with both T cell infiltration and response to immunotherapy, despite the well-established correlation of VEGF-C with worse prognosis in the absence of immunotherapy. Limitations of this study include uncertainty in the following: (i) the potential roles of other immune cell subsets that may be altered in VEGF-C-expressing tumors, including natural killer T cells, gd T cells, and especially various DC subsets that we found to be enriched; (ii) the extent to which numerous other cytokines that are altered in lymphangiogenic tumors contribute to immunotherapy potentiation; (iii) cell sources of VEGF-C in human tumors; and (iv) indirect effects of naïve T cell recruitment on the immune microenvironment [for example, competition with T reg cells for nutrients (44) or homeostatic cytokines such as IL-7 (45)]. These will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They also confirm relevance in human melanoma patients, in terms of VEGF-C correlating with both T cell infiltration and response to immunotherapy, despite the well-established correlation of VEGF-C with worse prognosis in the absence of immunotherapy. Limitations of this study include uncertainty in the following: (i) the potential roles of other immune cell subsets that may be altered in VEGF-C-expressing tumors, including natural killer T cells, gd T cells, and especially various DC subsets that we found to be enriched; (ii) the extent to which numerous other cytokines that are altered in lymphangiogenic tumors contribute to immunotherapy potentiation; (iii) cell sources of VEGF-C in human tumors; and (iv) indirect effects of naïve T cell recruitment on the immune microenvironment [for example, competition with T reg cells for nutrients (44) or homeostatic cytokines such as IL-7 (45)]. These will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CD25, the α-chain of the IL-2 receptor, is expressed at only intermediate/dim levels [ 1 ], questioning whether naïve-Tregs, like their memory counterparts, depend on IL-2 [ 2 ]. Moreover, Tregs per se typically express low levels of the α-chain of the IL-7 receptor (IL-7Rα), and there are controversial reports on the IL-7 impact on human and murine Tregs [ 18 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of recent studies in mice identified IL-7 as a necessary factor to sustain expression of high levels of CD25 at the T reg surface in vivo, thereby supporting the functional activity of effector T regs by increasing their IL-2 sensitivity [49,50].…”
Section: Discussionmentioning
confidence: 99%